Urban waste water treatment with classical coagulation and sand filtration - Magi Mercy; Astibha Brhane; Omprakash Sahu (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Pollution has significant impact on surrounding. Industrial and domestic wastewaters are the main sources of water pollutants that are responsible for various diseases. A number of methods are available in literature but expensive, due to that not feasible. The aim of this research work is to treat the grey wastewater with economical coagulant and filtration treatment methods. The coagulation process carries out with Jar test apparatus and filtration with normal filter. The results shows that alum reduced pH 6.5, turbidity 1.42 mg/L, biological oxygen demand 85mg/L and chemical oxygen demand 215 mg/L as well ferric chloride reduced pH 8, turbidity 0.771 mg/L, biological oxygen demand 60mg/l and chemical oxygen demand 130mg/L was achieved. At last both treatment are convenient to operate and economical to the pollutant level from urban area. Treated water can be recycling for agricultural and gardening purpose. It protects from unwanted discharge to controlled files and misquotes breeding.